P05 Cardiac safety of the trastuzumab biosimilar ABP 980 in women with HER2-positive early breast cancer in the LILAC study. (1st November 2019) - Kolberg, H-C; Colleoni, M; Savva Demetriou, G; Santi, P; Tesch, H; Fujiwara, Y; Tomasevic, Z; Hanes, V
Abstract : Introduction/Background: Although well-tolerated, trastuzumab can lead to severe heart failure in 2–4% of patients. In the phase 3 LILAC trial, trastuzumab biosimilar ABP 980 demonstrated similar efficacy, safety, and immunogenicity to trastuzumab reference product (RP) in women with HER2-positive early breast cancer. Here we report on cardiac safety of ABP 980 versus RP. Methodology: In the LILAC trial, all 725 patients randomly assigned to receive ABP 980 (n=364) or trastuzumab RP (n=361) were assessed for adverse events (AEs) every 3 weeks (Q3W) and for cardiac safety by left ventricular ejection fraction (LVEF) 2D echocardiogram every 3 months. LVEF decline was defined as the value decrease from study baseline by ≥10 percentage points and to <50%. After breast surgery, patients received investigational product (IP) Q3W for up to 1 year; ABP 980-treated patients continued ABP 980, and RP–treated patients either continued RP (n=190) or switched to ABP 980 (RP/ABP 980; n=171). Results: IP disposition was well balanced between treatment groups. Over the entire trial, 22 (3.1%) patients had LVEF decline by ≥10 percentage points from baseline and to <50%; no meaningful between-group differences were observed (ABP 980:10/359 [2.8%], RP: 6/184 [3.3%], RP/ABP 980: 6/171 [3.5%]). The incidence of cardiac AEs was low and comparable between treatment groups. One grade 3 cardiac failure event was reported in the RP/ABP 980 arm; another in the RP arm was coincident with LVEF decline. During the adjuvant phase, no patient discontinued IP due to cardiac failure. Conclusion: These pre-specified analyses confirm the tolerability of ABP 980 and demonstrate clinical similarity of ABP 980 and RP with respect to cardiac safety. The incidence of LVEF decline was consistent with the known cardiac safety profile of the RP. No new cardiac safety signals were observed whether patients were on ABP 980 or switched from RP to ABP 980. Disclosure: H-C Kolberg received consulting fees from Novartis, GSK, Pfizer, Carl Zeiss Meditec, Genomic Health, LIV Pharma, SurgVision, Roche, TEVA, Theraclion, Amgen Inc, Janssen; honoraria from AstraZeneca, Amgen, Theraclion, ZEISS, Novartis, Pfizer, Roche, Genomic Health, SurgVision; contracted Research with Amgen Inc.; and holds stocks in Theraclion and Phaon Scientific. M. Colleoni received honoraria from Novartis; consulting fees from Pierre Fabre, Pfizer, OBI Pharma, Puma Biotechnology, Celldex, AstraZeneca; and contracted Research with Amgen Inc. G. Demetriou received consulting fees from AstraZeneca and Profmed; received honoraria from Roche/Genentech; and honoraria for Speakers' bureau from Merck Serono. P. Santi declares no conflict of interest. H. Tesch received consulting fees as advisor and Research funding from Amgen. Y. Fujiwara received consulting fees from Bristol-Myers Squibb Japan and AstraZeneca KK; and honoraria from AstraZeneca KK, Daiichi Sankyo, and SRL Diagnostics. Z. Tomasevic received honoraria and consulting fees from Roche, Pfizer, and Novartis; honoraria for Speakers' Bureau from AstraZeneca, Roche, and Pfizer; and contracted Research with Amgen Inc. V. Hanes is an employee of Amgen and holds stock in Amgen.